IRG1/itaconate enhances efferocytosis by activating Nrf2-TIM4 signaling pathway to alleviate con A induced autoimmune liver injury - Liwu Zeng; Yaxin Wang; Yongzhou Huang; Wenchang Yang; Pei Zhou; Yaqi Wan; Kaixiong Tao; Ruidong Li (Cell Communication and Signaling)
Abstract Immune response gene 1 (IRG1) is highly expressed in mitochondria of macrophages in a pro-inflammatory state. IRG1 and its metabolites play important roles in infection, immune-related diseases and tumor progression by exerting resistance of pathogens, attenuating inflammation and producing antioxidant substances through various pathways and mechanisms. IRG1 deficiency aggravates liver injury. Efferocytosis is a vital mechanism for preventing the progression of inflammatory tissue damage. However, the mechanism by how IRG1/itaconate regulates efferocytosis in autoimmune hepatitis has yet to be fully understood. Therefore, we explored the influence of IRG1-/- on efferocytosis and its effects on regulating the nuclear factor erythroid 2-associated factor 2 (Nrf2)-T-cell immunoglobulin domain and mucin domain 4 (TIM4) pathway and autoimmune liver injury. An autoimmune hepatitis model was established by injecting Con A into wild-type and IRG1-/- mice via the tail vein. Liver injury and inflammatory response were assessed. The efferocytosis role of IRG1-/- macrophages and its potential regulatory mechanisms were also analysed. Exogenous 4-octyl itaconate (OI) supplementation promoted the expression of Nrf2 and TIM4 and restored IRG1-/- bone marrow-derived macrophage (BMDM) efferocytosis, whereas inhibition of Nrf2 mediated by ML385 led to impaired efferocytosis of BMDMs, decreased expression of TIM4, and aggravated liver inflammation injury. Additionally, after supplementing Nrf2-/- BMDMs with exogenous OI, we evaluated the changes in its efferocytosis effect, efferocytosis did not change, and the protective effect of OI disappeared. However, when TIM4 was blocked, the efferocytotic effect of BMDMs was attenuated, inflammatory liver injury and oxidative stress were aggravated. OI promoted the transformation of macrophages into M2 macrophages, and this was inhibited when TIM4 was blocked. To our best understanding, this is the initial exploration to show that TIM4, a downstream molecule of the IRG1/itaconate-Nrf2 pathway, regulates macrophage efferocytosis. These findings suggest a new mechanism and potential treatment for promoting the resolution of inflammation and efferocytosis in autoimmune hepatitis.